Investment Strategy, Business Capital and Income Against Recession Risk Through Government Regulations - Supardi, Supardi; Sriyono, Sriyono; Qomarudin, Ahmad (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This research explores investment strategies, working capital, and income during economic recessions, emphasizing the role of government policies in achieving Sustainable Development Goal (SDG) No. 9, which focuses on resilient infrastructure, sustainable industrialization, and innovation. Through explanatory analysis, the study examines the relationship between investment approaches and economic uncertainty. The findings indicate that, during recessions, investment strategies focused on critical infrastructure can enhance economic resilience and support long-term growth. Flexible and adaptive working capital management is also crucial for businesses to navigate market volatility and mitigate the risk of instability. The study reveals that investment strategies and income are influenced by government regulations, whereas working capital does not have a direct impact on these regulations. However, both investment strategies and venture capital affect recession risk through government regulation. Additionally, government regulation plays a mediating role in the impact of income on recession risk, underscoring its importance in stabilizing the economy during uncertain times. These findings highlight the need for innovative investment approaches and strategic financial management to build economic resilience and advance SDG No. 9. In conclusion, appropriate government policies and effective capital management can help reduce the adverse effects of economic downturns, ensuring a more stable economic environment during periods of uncertainty.